Diet of breeding Eleonora's falcon Falco eleonorae in Algeria: Insights for the autumn trans-Mediterranean avian migration - Samraoui, Boudjéma; Kayser, Yves; Touati, Laïd; Samraoui, Farrah; Boucheker, Abdennour; El-Serehy, Hamed A; Samraoui, Kenz Raouf (Ecology and evolution, 2022)
How environmental changes are affecting bird population dynamics is one of the most challenging conservation issues. Dietary studies of top avian predators could offer scope to monitor anthropogenic drivers of ecosystem changes. We investigated the diet of breeding Eleonora's falcon in an area of Northeastern Algeria in the years 2010-2012. Feathers and insect remains originating from prey plucking behavior were analyzed, providing insights into the seasonally changing diet of this raptor, as well as the trans-Mediterranean avian migration. A total of 77 species of birds (16 Sylviidae, 11 Turdidae, and 4 Emberizidae), 3 species of insects, and 1 lizard were identified among prey remains, reflecting a diverse diet. Diet composition and prey abundance varied seasonally, faithfully correlating with the passage of migrant birds as recorded from bird ring recoveries. Our findings suggest that dietary studies of predators might be deployed to investigate changes in bird migration. We discuss our results in the context of trans-Mediterranean migration, with early-season prey mainly comprising trans-Saharan migrants (Apus apus and Merops apiaster) and late-season prey being dominated by Mediterranean winter migrants (Erithacus rubecula, Turdus philomelos, Sylvia atricapilla, and Sturnus vulgaris). Notably, we observed a significant reduction in species richness of passerine remains in 2012, potentially highlighting a decline in the diversity of avian migrants.
Keywords: trans‐Mediterranean migration; autumn migration; trans‐Saharan migrants; diet; passerine